Odpowiedzi

2009-11-26T17:23:20+01:00
A) 3(a+b)+(a-2b)= 3a+3b+a-2b=4a+b
b)-4(x-z)-(x+y)=-4x+4z-x-y=-5x+4z-y
c)5(4x-7)+(7-4x)=20x-35+7-4x=16x-28
d)(4x-y)-2(x+y)=4x-y-2x-2y=2x-3y
e)2(3x-2y+3z)-5(x-y-z)=6x-4y+6z-5x+5y+5z=x+y+11z
f)4x(x-y-z)-2x(4x-y+z)=4x²-4xy-4xz-8x²+2xy-2xz=-4x²-2xy-6xz
Najlepsza Odpowiedź!
2009-11-26T17:23:52+01:00
A) 3(a+b)+(a-2b)= 3a+3b+a-2b=4a+b
b) -4(x-z)-(x+y)=-4x+4z-x-y=-5x+4z-y
c) 5(4x-7)+(7-4x)=20x-35+7-4x=16x-28
d) (4x-y)-2(x+y)=4x-y-2x-2y=2x-3y
e) 2(3x-2y+3z)-5(x-y-z)=6x-4y+6z-5x+5y+5z=x+y+11z
f) 4x(x-y-z)-2x(4x-y+z)=4xdo2-4xy-4xz-8xdo2+2xy-2xz=-4xdo2-2xy-6xz

PROSZĘ!
2009-11-26T17:27:37+01:00
A) 3(a+b)+(a-2b) = 3a+3b+a-2b = 4a+b
b) -4(x-z)-(x+y) = -4x+4z-x-y = -5x+4z-y
c) 5(4x-7)+(7-4x) = 20x-35+7-4x = 16x-28
d) (4x-y)-2(x+y) = 4x-y-2x-2y = 2x-3y
e) 2(3x-2y+3z)-5(x-y-z) = 6x-4y+6z-5x+5y+5z = x+y+11z
f) 4x(x-y-z)-2x(4x-y+z) = 4x²-4xy-4xz-8x²+2xy-2xz = -4x²-2xy-6xz